HUBUNGAN KUALITAS BIOLOGI, KIMIA, FISIKA AIR SUMUR DENGAN KEPADATAN PENDUDUK DI KABUPATEN JEMBER - Avishia Prisma Yulivarta; Joko Waluyo; Mochammad Iqbal (Jurusan Pendidikan MIPA FKIP Universitas Jember, 2019)
Biologically, clean water can be said to be suitable for use if the water does not contain pathogenic microorganisms that are harmful to human health. Chemically, consumable water is water that has a pH of 6.5-8.5. Physically it also needs attention. This study aims to find out how the relationship between the quality of biology, chemistry, physics, in Jember Regency well water based on the Republic of Indonesia PERMENKES No.492/MENKES/PER/IV/2010